2018
DOI: 10.1155/2018/1672501
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Vitrectomy Combined with Internal Limiting Membrane Peeling for the Treatment of Idiopathic Macular Hole with Air or C3F8 Intraocular Tamponade

Abstract: Purpose The treatment of idiopathic macular holes has been basically modeled, and vitreoretinal surgery is recognized as an effective treatment. However, the postoperative tamponade of gas will still make the patient uncomfortable and may have related complications. The purpose of this study is to investigate whether air as an intraocular tamponade is equivalent to gas and what advantages may exist. Methods A retrospective study was performed in one hundred and ninety-eight patients from 2013 to 2017; 112 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…There was a significant increase in the IOP in operated eyes between baseline and postoperative day 2, which seems to be due to the effect of surgery itself, such as corneal edema or postoperative inflammation. In addition, as noted in previous studies [17][18][19], the IOP increase in surgically treated eyes could be attributed to the influence of FDP. Furthermore, the IOP significantly decreased between postoperative days 2 and 7 in both eyes, but the degree of descent was higher in the contralateral eyes.…”
Section: Plos Onesupporting
confidence: 72%
“…There was a significant increase in the IOP in operated eyes between baseline and postoperative day 2, which seems to be due to the effect of surgery itself, such as corneal edema or postoperative inflammation. In addition, as noted in previous studies [17][18][19], the IOP increase in surgically treated eyes could be attributed to the influence of FDP. Furthermore, the IOP significantly decreased between postoperative days 2 and 7 in both eyes, but the degree of descent was higher in the contralateral eyes.…”
Section: Plos Onesupporting
confidence: 72%
“…To maximize the effects of gas and improve the closure rate of macular hole, long-lasting gas tamponades, such as SF6, C2F6, and C3F8, are used as standard practice in macular hole surgery [20]. Recently, some studies have demonstrated that room air can have similar outcomes to long-lasting gas, but the conclusions of these studies are limited because they only macular holes with small diameters were included [8,9,10]. Gesseret al reported that the initial closure rate for air as a tamponade for MH surgery was only 79%, about 10% lower than that reported in other studies with long-acting gas tamponades [11].…”
Section: Resultsmentioning
confidence: 99%
“…Lens opacification was another complication of intraocular gas filling, Chen et al found a higher rate of transient lens opacity in the C3F8 group than that of air group after the surgery [10]. Studies showed that cataract surgery performed after macular hole repair could cause complications due to intraoperative difficulties during phacoemulsification, which arise from the absence of vitreous support in a vitrectomized eye and the increased risk of zonular and/or posterior capsular insult [24].Moreover, cataract surgery following macular hole repair may lead to postoperative reopening of the macular hole in about 20% of patients, especially if there are complications involving cystoid macular edema.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of air tamponade to successfully treat small MHs has been described in some studies. [9][10][11][12] However, air is still used very rarely for large MHs. In this study, sterile air was used as a tamponade for medium-large MHs, and the results indicate that this surgical approach achieved favourable results, suggesting that air tamponade is a safe and effective treatment for medium-large MHs.…”
Section: Discussionmentioning
confidence: 99%